Competition law in crisis : the antitrust response to economic shocks - Wardhaugh, Bruce, 1960- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
A common criticism of the competition rules posed by EU authorities is that they are too inflexible, thereby prohibiting adequate responses to economic and industrial shocks. Competition Law in Crisis challenges this suggestion through an examination of competition responses to crises past and present. With an analysis spanning the response of UK and EU competition authorities to the economic and commercial outfall of the 2008 financial crisis, the COVID-19 pandemic, and potential responses to the climate crisis in the context of post-Brexit British industrial policy, the book argues that relaxing the competition regime is precisely the wrong response. The rigidity of competition rules in the UK and EU has both normative and positive implications for not just the methodology used in competition analysis, but also the role of competition law within the legal order of both jurisdictions. The book concludes with a discussion of the place of the competition in the UK's and EU's legal order.
Legal framework -- The pre-more economic approach to competition's role in crisis management -- The Post-MEA relationship between competition law and crisis management -- The financial crisis of 2008 -- The covid crisis -- Brexit : squandered opportunities? -- Environment, sustainability goals, and the climate crisis.
Title from publisher's bibliographic system (viewed on 08 Aug 2022).
Keywords: Antitrust law -- Great Britain; Competition, Unfair -- Great Britain; Restraint of trade -- Great Britain; Competition -- Great Britain